The mediating role of critical thinking skills in the relationship between technology-based learning, digital competence, and academic achievement - Sulfiani Masri; Leonardo Davidsi Sipayung; Andhi Febisatria (Journal of Research on English and Language Learning (J-REaLL), 2026)
Teaching and learning approaches have developed alongside the growing adoption of digital technologies in higher education. However, the effect of these technologies on students' academic achievement remains unclear. Previous research has yielded mixed findings. Several studies suggest that digital competence and technology-based learning enhance academic performance, while others report only marginal advantages, especially for students with lower cognitive abilities. These discrepancies highlight a notable gap in the literature, as previous research has largely concentrated on academic performance, digital learning, and digital competence separately without sufficiently explaining the mechanisms that link them. This limitation leads to an incomplete understanding of how digital technologies improve learning outcomes and may contribute to inefficient implementation in educational settings. Therefore, there is a need for a more integrated framework to clarify these relationships. This study proposes a model that views critical thinking as a crucial mediating mechanism that connects digital competence and technology-based learning to academic achievement. This study employs a survey of 264 purposively selected undergraduate students from a university in Makassar, with data analyzed using SEM-PLS. The findings demonstrate that technology-based learning and digital competence significantly affect academic achievement, both directly and indirectly through critical thinking as a mediating variable. Overall, this study emphasizes the importance of incorporating critical thinking into technology-based learning to promote academic achievement in higher education and provides empirical evidence of the role of cognitive processes in shaping digital learning outcomes.